THE ORGANIZATIONAL ACTIVITIES OF ACADEMICIAN S.K. KAMALOV AS THE HEAD OF A HIGHER EDUCATION INSTITUTION - Abatov, Askar Reyimbaevich (SCIENCE and SOCIETY, 2026)
The pedagogical activity of Sabyr Kamalov played an important role in the development of the education system and historical science in Karakalpakstan. As a teacher, head of a higher education institution, and academician, he made a significant contribution to the training of national specialists, the improvement of history teaching methodology, and directly supervised the development of the first curricula and textbooks on the history of Karakalpakstan. The article highlights, through specific examples, the activities of Academician S.Kamalov as the head of Nukus State Pedagogical Institute.
Keywords: Academician S.K.Kamalov; managerial activity; history; historiography; karakalpak people; school; mentor; apprentice